Feasibility and efficacy of low‐dose pegfilgrastim for CD34+ cell mobilization in lymphoma. Issue 5 (29th July 2020) - Goto, Hideki; Hidaka, Daisuke; Yamamoto, Satoshi; Hayasaka, Koji; Michimata, Rie; Kagawa, Ikuko; Sunagoya, Kana; Iijima, Hiroaki; Hayase, Eiko; Shiratori, Souichi; Okada, Kohei; Sugita, Junichi; et al.
Abstract: Background: Pegfilgrastim has equivalent efficacy to daily granulocyte colony‐stimulating factor (G‐CSF) in enhancing neutrophil recovery after chemotherapy, but data on its use for peripheral blood stem cell (PBSC) mobilization are limited. We evaluated the safety and efficacy of CD34 + PBSC mobilization by low‐dose (3.6 mg) pegfilgrastim after chemotherapy in patients with malignant lymphoma. Study Design and Methods: Twenty patients with malignant lymphoma were enrolled in this study. Cytotoxic chemotherapy was started on day 1, and 3.6 mg of pegfilgrastim was subcutaneously administered on day 7. CD34 + cells were counted in the peripheral blood daily from days 11 to 14 using a flow cytometric analysis. Results: In 19 of the 20 patients (95%), the CD34 + cell counts in the peripheral blood exceeded 10 × 10 6 /L, with a mean value of 20.3 on day 11, 38.0 on day 12, 40.3 on day 13, and 40.1 on day 14. Older age was associated with lower maximum CD34 + cell mobilization. The most frequent adverse events associated with pegfilgrastim were back pain, nausea, appetite loss, and lactate dehydrogenase elevation. Conclusion: Our data indicated that a single dose of 3.6 mg pegfilgrastim on day 7 after chemotherapy safely and effectively mobilized CD34 + cells.